Is Ghana Ready to Attain Sustainable Development Goal (SDG) Number 7?—A Comprehensive Assessment of Its Renewable Energy Potential and Pitfalls - Michael Acheampong; Qiuyan Yu; Funda Cansu Ertem; Lucy Deba Enomah Ebude; Shakhawat Tanim; Michael Eduful; Mehrdad Vaziri; Erick Ananga (Energies, 2019)
Ghana has declared support for the UN Sustainable Development Goal (SDG) number seven which most importantly target ensuring universal access to affordable, reliable and modern energy services. This target presents a formidable challenge to Ghana because the country still relies mainly on traditional biomass as its primary source of energy coupled with a chronically fragile hydropower sector. In this study, we assess Ghana’s potential in achieving sustainable goal number seven. Specifically, we comprehensively review the breakthroughs and impediments Ghana has experienced in its efforts towards improving its renewable energy potential. We note that while Ghana has made significant stride toward attaining energy efficiency, its effort at large-scale biofuel development hit a snag due to issues of “land grabbing„ emanating both from local and foreign entities. In another breadth, several pilot studies and research initiatives have demonstrated the possibility of diversifying the energy sector with other renewable energy options including solar, wind, and small hydro. In spite of challenges encountered with the development of biofuels, our review concludes that Ghana retains vast reserves of renewable energy potential, which can be harnessed with the constantly improving technological advancements as it pursues SDG number seven.